2021
DOI: 10.3389/fnut.2021.633987
|View full text |Cite
|
Sign up to set email alerts
|

The Aging Muscle in Experimental Bed Rest: A Systematic Review and Meta-Analysis

Abstract: Background: Maintaining skeletal muscle mass and function in aging is crucial for preserving the quality of life and health. An experimental bed rest (BR) protocol is a suitable model to explore muscle decline on aging during inactivity.Objective: The purpose of this systematic review and meta-analysis was, therefore, to carry out an up-to-date evaluation of bed rest, with a specific focus on the magnitude of effects on muscle mass, strength, power, and functional capacity changes as well as the mechanisms, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 80 publications
2
29
0
2
Order By: Relevance
“…Our study has several limitations. First, the number of investigated participants that underwent the 14-day bed rest protocol is relatively low, but is comparable to many other studies that compared young vs. older participants (Erim et al, 1999, 20 participants;Connelly et al, 1999, 12 participants;Vaillancourt et al, 2003, 30 participants;Kallio et al, 2012, 17 participants;Castronovo et al, 2018, 20 participants) as well as to other bed rest studies where the number of participants ranged from 6 to 16 (Di Girolamo et al, 2021). This is partially justified by the complexity and stress of the prolonged bed rest that needs to be carried out in a hospital setting with 24-h medical inspection and care.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our study has several limitations. First, the number of investigated participants that underwent the 14-day bed rest protocol is relatively low, but is comparable to many other studies that compared young vs. older participants (Erim et al, 1999, 20 participants;Connelly et al, 1999, 12 participants;Vaillancourt et al, 2003, 30 participants;Kallio et al, 2012, 17 participants;Castronovo et al, 2018, 20 participants) as well as to other bed rest studies where the number of participants ranged from 6 to 16 (Di Girolamo et al, 2021). This is partially justified by the complexity and stress of the prolonged bed rest that needs to be carried out in a hospital setting with 24-h medical inspection and care.…”
Section: Discussionsupporting
confidence: 78%
“…Experimental bed rest is a gold standard ground-based model for studying the effects of microgravity, as well as interaction between aging and disuse (Di Girolamo et al, 2021). Post bed rest decreases of muscle mass and strength (Koren, 2015;Pišot et al, 2016;Rejc et al, 2018;Marusic et al, 2021), as well as performance and neural drive (Duchateau, 1995) were reported in the past, along with the damaged neuromuscular junctions and muscle denervation (Monti et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental BR is one of the most appropriate methods to study the consequences of immobilization in a standardized and controlled environment (35). This approach has been recognized to be of potential clinical relevance for mimicking hospitalrelated physical inactivity since it allows differentiating the catabolic effects induced by a disease from those secondary to skeletal muscle disuse (35).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental BR is one of the most appropriate methods to study the consequences of immobilization in a standardized and controlled environment (35). This approach has been recognized to be of potential clinical relevance for mimicking hospitalrelated physical inactivity since it allows differentiating the catabolic effects induced by a disease from those secondary to skeletal muscle disuse (35). The study of healthy volunteers in facilities that allow a controlled modification of the amount of oxygen in the air in both bed rest and/or ambulatory conditions can be considered an appropriate model to investigate the separate and the combined effect of hypoxia and muscle disuse (28,36,37).…”
Section: Introductionmentioning
confidence: 99%
“…With advancements in technology from the molecular to the modeled system level, neuromechanics is strategically positioned to advance the diagnoses and prognoses of clinical conditions and analyze and increase sports performance. The Neuromechanics section will welcome submissions to report novel data on: • Force generation in fresh and fatigued states by skeletal muscle from the cellular to system level and its adaptation to treatments, supplemented by neurophysiological measurements in health and disease [12,13]; • Dynamic characterization of tendon properties and tracking the adaptation of tendons to interventions using high resolution imaging [14-18];…”
mentioning
confidence: 99%